Seasonal effects on growth and product quality in Atlantic salmon fed diets containing terrestrial oils as assessed by a long-term, on-farm growth trial - Tom Mock; David Francis; Matt Jago; Paige Miles; BD Glencross; RP Smullen; Russell Keast; GM Turchini (2021)
Seasonal effects on growth and product quality in Atlantic salmon fed diets containing terrestrial oils as assessed by a long-term, on-farm growth trial